Cigar Waste Control Based on Statistical Process Control (SPC) for Achieving a Green and Sustainable Industry in Jember Regency - Wahyono, Nanang Dwi; Kurniawati, Dewi; Harkat, Avisenna; Wardani, Dyah Kusuma; Atmajaya, Aditya Wahyu Winadi; Pratama, Fredy Eka Ardhi (P3M Politeknik Negeri Jember, 2025)
The cigar industry in Jember Regency is recognized as one of Indonesia’s major tobacco production centers, contributing significantly to the regional economy. However, its production process generates substantial waste, including rejected leaves, stems, tobacco dust, and packaging waste, which may pose environmental challenges. This study aims to apply Statistical Process Control (SPC) to monitor and control cigar waste as part of efforts to promote circular economy practices and sustainable industry. A descriptive quantitative method was employed, with data collected through direct observation, structured interviews, and statistical analysis using X-bar, R, and I-MR control charts. Results indicate that most production processes remain within control limits, although special variations were detected in wrapper leaf quality and tobacco moisture content. Process capability analysis revealed that leaf scraps (Cpk = 1.69) met the required standards, whereas defective cigars (Cpk = 0.28) required corrective actions through workforce training and SOP standardization. The cause-and-effect (Ishikawa) diagram identified key contributing factors including manpower, machines, materials, methods, and environment. Findings highlight that implementing SPC not only reduces production costs and improves efficiency but also creates opportunities for utilizing waste into derivative products such as hand-rolled kretek cigarettes (SKT), thereby supporting green industry practices. Thus, SPC can serve as a practical and strategic model for sustainable quality control in Jember’s cigar industry.